Major hazard control : a practical manual : an ILO contribution to the International Programme on Chemical Safety of UNEP, ILO, WHO (IPCS) (Geneva, 1988)
Deals with the safety aspects of siting, planning, design, construction and operation of plants, explaining how to identify major hazards in installations.